2021
DOI: 10.1038/s41421-021-00284-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the human ABCB6 transporter

Abstract: ABCB6 plays a crucial role in energy-dependent porphyrin transport, drug resistance, toxic metal resistance, porphyrin biosynthesis, protection against stress, and encoding a blood group system Langereis antigen. However, the mechanism underlying porphyrin transport is still unclear. Here, we determined the cryo-electron microscopy (cryo-EM) structures of nanodisc-reconstituted human ABCB6 trapped in an apo-state and an ATP-bound state at resolutions of 3.6 and 3.5 Å, respectively. Our structures reveal a uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…1A ). In agreement with the results of previous studies ( Song et al, 2021 ; Wang et al, 2020 ), our data indicated that at saturating concentrations (100 µM PPIX or 50 µM CPIII), the metal-free porphyrins modestly stimulated the ATPase activity of ABCB6-∆TMD0 approximately 2- to 3-fold ( Figs. 1B and 1C ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…1A ). In agreement with the results of previous studies ( Song et al, 2021 ; Wang et al, 2020 ), our data indicated that at saturating concentrations (100 µM PPIX or 50 µM CPIII), the metal-free porphyrins modestly stimulated the ATPase activity of ABCB6-∆TMD0 approximately 2- to 3-fold ( Figs. 1B and 1C ).…”
Section: Resultssupporting
confidence: 93%
“…2A and 2B), but the TMDs swing towards each other (~4°), resulting in a somewhat reduced separation between the two NBDs (Fig. 2C) (Song et al, 2021;Wang et al, 2020). The most significant structural changes are concentrated near the central cavity where we could assess the EM density of CPIII at the inner leaflet-cytosol interface (Fig.…”
Section: Model Building Strategy Of Cpiii Bound To Abcb6-∆tmd0mentioning
confidence: 98%
See 1 more Smart Citation
“…This structure revealed an inward-facing conformation for At Atm3 similar to those observed for the inward-facing conformations for Sc Atm1 (PDB ID: 4myc) and Na Atm1 (PDB ID: 6vqu) with overall alignment root mean square deviations (rmsds) for the dimer of 2.6 Å ( Figure 2—figure supplement 2a, b ) and 2.1 Å ( Figure 2 ), respectively, and half-transporter alignment rmsds of 2.3 and 2.0 Å ( Figure 2—figure supplement 2c ), respectively. The primary distinction between these structures is the presence of an approximately 20 amino acid loop between TM1 and TM2 of At Atm3 that would be positioned in the intermembrane space and is absent from the structures of ABCB7 ( Jumper et al, 2021 ; Varadi et al, 2022 ), ABCB6 ( Song et al, 2021 ), Sc Atm1 ( Srinivasan et al, 2014 ), and Na Atm1 ( Lee et al, 2014 ; Figure 2—figure supplement 3 ). While the functional relevance of this loop in At Atm3 is not known, structural characterization of PglK, a lipid-linked oligosaccharide flippase, revealed a comparably positioned external helix between TM1 and TM2 that was implicated in substrate flipping ( Perez et al, 2015 ), suggestive that the corresponding loop could also have a functional or structural role in At Atm3.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to oxidative damage, mitochondrial failure in AHP could also be driven by cytochrome dysfunction due to heme depletion. Of note, heme is yielded in mitochondria: following an initial series of reactions in the cytosol, coproporphyrin III is imported in mitochondria by ABCB6, a homodimeric porphyrin transporter located in the outer mitochondrial membrane, to undergo the final steps of heme biosynthesis [ 96 ]. Several alterations in brain oxidative phosphorylation have been reported in T1/T2 mice, with an increase of Complex II activity in the basal state, and a significant reduction of all four complexes after treatment with phenobarbital, compared to wild-type controls [ 97 ].…”
Section: Heme Deficiency-induced Dysfunctionmentioning
confidence: 99%